Penggunaan Scratch dalam Pengembangan Media Pembelajaran Aljabar pada Siswa Kelas VII SMP Negeri 50 Jakarta - Carmela Grace Alesandra Mone (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
A preliminary study of 54 seventh-grade students at SMP Negeri 50 in Jakarta found that the lack of interactive media in mathematics instruction made it difficult for students to understand abstract concepts such as algebra. The purpose of this study was to develop a Scratch-based algebra learning tool and to evaluate its practicality and validity. Needs analysis, design, product development, expert validation, and practicality testing were part of a quantitative approach using a research and development methodology (Research and Development Level 2). While subject matter experts, language experts, and media experts conducted the validation, students in 7th Grade Class A and 7th Grade Class E took the practical test. The results showed that the average validity score was 4.10, falling within the “valid” category, and the average practicality score was 3.81, falling within the “practical” category. The results indicate that block-based learning platforms such as Scratch are suitable for supporting algebra instruction in 7th grade. This conclusion suggests that block-based visual programming platforms like Scratch can serve as an effective alternative to help students understand abstract mathematical concepts and support the adoption of technology in 21st-century education.